Enhancing the Quality of Religious Education through Qur'an Education Park (TPQ) Learning in Village Communities - Masrifatin, Yuni; Fathurrohman, Amang; Hasan, Ziyaana; Husna, Maleek (STAI Miftahul ULa Nganjuk, 2024)
This community service program focuses on improving religious education quality at Taman Pendidikan Al-Qur'an (TPQ) in Bangsri Village. The main issue addressed is the limited resources and outdated teaching methods in local TPQs. The objective is to enhance the quality of Quranic education by empowering the community, particularly TPQ teachers, through training and the application of effective teaching methods. The program employs the Asset-Based Community Development (ABCD) approach, utilizing local resources and community participation to optimize learning processes. The community service includes identifying local assets, providing teacher training on Tajwid (proper Quranic pronunciation), and involving community members in supporting educational activities. As a result, there was a significant improvement in students' Quranic reading skills and teaching effectiveness. The initiative also fostered greater community involvement in supporting religious education, contributing to the overall development of the village's educational system.